DDPH inhibited L-type calcium current and sodium current in single ventricular myocyte of guinea pig - Hu Xiao-Dong; Qian Jia-Qing (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of 1-(2, 6-dimethylphenoxy)-2-(3,4-dimethoxyphenyl-ethylamino)propane hydrochloride (DDPH) on L-type calcium current (ICa) and sodium current (INa), and to compare its inhibitory potency with verapamil and mexiletine. Methods: Whole-cell patch clamp technique was used to record ICa and INa in a single ventricular myocytes of guinea pig. Results: (1) DDPH (3 - 300 micromol . L-1) decreased ICa at 0 mV in a concentration-dependent manner with an IC50 value of 28.5 micromol . L-1 (95 % confidence limits: 14.3 - 42.7 micromol . L-1, n = 8 cells from 8 guinea pigs). Verapamil (0.3 - 30 micromol . L-1) reduced ICa with an IC50 value of 1.8 micromol . L-1 (95 % confidence limits: 1.3 - 2.3 micromol . L-1, n = 6 cells from 6 guinea pigs). Mexiletine 100 micromol . L-1 did not affect ICa (n = 5 cells from 5 guinea pigs, P > 0.05). The degree of use-dependent blocking effect of DDPH 30 micromol/L on ICa was 58 % +/- 13 % (n = 5 cells from 5 guinea pigs, P < 0.01) at 1 Hz and 76 % +/- 11 % (n = 5 cells from 5 guinea pigs, P < 0.01) at 3 Hz. (2) DDPH (20 - 320 micromol . L-1) could also block INa in a concentration-dependent manner with an IC50 value of 89.0 micromol . L-1 (95 % confidence limits: 68.7 - 109.3 micromol . L-1, n = 9 cells from 9 guinea pigs). The IC50 value of mexiletine was 32.2 micromol . L-1 (95 % confidence limits: 11.7 - 52.7 micromol . L-1, n = 5 cells from 5 guinea pigs). Verapamil at the concentration of 10 micromol . L-1 did not affect INa (n = 5 cells from 5 guinea pigs, P > 0.05). The blocking effect of DDPH 80 micromol/L on INa was non use-dependent. Conclusion: DPH exhibited inhibitory effects on both ICa and INa, but its inhibitory effect on ICa was weaker than verapamil, and on INa was weaker than mexiletine.